Giúp với ạ!! đang cần gấp ạ!

Giúp với ạ!!
đang cần gấp ạ!
giup-voi-a-dang-can-gap-a

0 thoughts on “Giúp với ạ!! đang cần gấp ạ!”

  1. Giải thích các bước giải:

    Ta có:

    \(\begin{array}{l}
    1,\\
    a,\\
    \dfrac{{{x^2} – 13}}{{x + \sqrt {13} }} = \dfrac{{\left( {x – \sqrt {13} } \right)\left( {x + \sqrt {13} } \right)}}{{x + \sqrt {13} }} = x – \sqrt {13} \\
    b,\\
    \dfrac{{{x^2} + 2\sqrt 3 .x + 3}}{{{x^2} – 3}} = \dfrac{{{{\left( {x + \sqrt 3 } \right)}^2}}}{{\left( {x – \sqrt 3 } \right)\left( {x + \sqrt 3 } \right)}} = \dfrac{{x + \sqrt 3 }}{{x – \sqrt 3 }}\\
    c,\\
    \sqrt {9{x^2}}  – 2x = \sqrt {{{\left( {3x} \right)}^2}}  – 2x = \left| {3x} \right| – 2x =  – 3x – 2x =  – 5x\\
    d,\\
    \sqrt {4 – 2\sqrt 3 }  – \sqrt 3  = \sqrt {3 – 2.\sqrt 3 .1 + 1}  – \sqrt 3  = \sqrt {{{\left( {\sqrt 3  – 1} \right)}^2}}  – \sqrt 3  = \left( {\sqrt 3  – 1} \right) – \sqrt 3  =  – 1\\
    e,\\
    x – 4 + \sqrt {16 – 8x + {x^2}}  = x – 4 + \sqrt {{x^2} – 2.x.4 + {4^2}}  = \left( {x – 4} \right) + \sqrt {{{\left( {x – 4} \right)}^2}}  = \left( {x – 4} \right) + \left| {x – 4} \right| = \left( {x – 4} \right) + \left( {x – 4} \right) = 2.\left( {x – 4} \right)\\
    f,\\
    \sqrt {11 + 6\sqrt 2 }  – 3 + \sqrt 2  = \sqrt {9 + 2.3.\sqrt 2  + 2}  – 3 + \sqrt 2  = \sqrt {{{\left( {3 + \sqrt 2 } \right)}^2}}  – 3 + \sqrt 2  = \left( {3 + \sqrt 2 } \right) – 3 + \sqrt 2  = 2\sqrt 2 \\
    2,\\
    a,\\
    \sqrt {x + 4}  = 2\,\,\,\,\,\,\,\,\,\left( {x \ge  – 4} \right)\\
     \Leftrightarrow x + 4 = 4\\
     \Leftrightarrow x = 0\\
    b,\\
    \sqrt {2x – 1}  = \sqrt 7 \,\,\,\,\,\,\,\left( {x \ge \dfrac{1}{2}} \right)\\
     \Leftrightarrow 2x – 1 = 7\\
     \Leftrightarrow x = 4\\
    c,\\
    \sqrt {x – 10}  =  – 2\,\,\,\,\,\,\,\,\,\,\,\,\,\left( {x \ge 10} \right)\\
    \sqrt {x – 10}  \ge 0 \Rightarrow ptvn\\
    d,\\
    \sqrt {4 – 7x}  = 13\,\,\,\,\,\,\,\,\left( {x \le \dfrac{4}{7}} \right)\\
     \Leftrightarrow 4 – 7x = 169\\
     \Leftrightarrow 7x =  – 165\\
     \Leftrightarrow x =  – \dfrac{{165}}{7}\\
    3,\\
    a,\\
    \dfrac{{\sqrt {63{y^3}} }}{{\sqrt {7y} }} = \sqrt {\dfrac{{63{y^3}}}{{7y}}}  = \sqrt {9{y^2}}  = \sqrt {{{\left( {3y} \right)}^2}}  = \left| {3y} \right| = 3y\\
    b,\\
    \dfrac{{\sqrt {49{a^6}{b^4}} }}{{\sqrt {128{a^8}{b^4}} }} = \sqrt {\dfrac{{49{a^6}{b^4}}}{{128{a^8}{b^4}}}}  = \sqrt {\dfrac{{{7^2}}}{{{2^7}.{a^2}}}}  = \dfrac{1}{{\sqrt 2 }}\left| {\dfrac{7}{{{2^3}.a}}} \right| = \dfrac{7}{{8\sqrt 2 a}}\\
    c,\\
    \sqrt {\dfrac{{x – 2\sqrt x  + 1}}{{x + 2\sqrt x  + 1}}}  = \sqrt {\dfrac{{{{\left( {\sqrt x  – 1} \right)}^2}}}{{\left( {\sqrt x  + 1} \right)}}}  = \left| {\dfrac{{\sqrt x  – 1}}{{\sqrt x  + 1}}} \right| = \dfrac{{\left| {\sqrt x  – 1} \right|}}{{\sqrt x  + 1}}
    \end{array}\)

    Reply

Leave a Comment